SIDE EFFECTS OF SECOND-LINE ANTITUBERCULOSIS DRUGS IN MULTI-DRUG RESISTANCE (MDR) TUBERCULOSIS PATIENTS - Tamzil, Nia Savitri; Lorenza, Geofanny; Andriani, R.A. Linda; Theodorus, Theodorus; Sudarto, Sudarto; Lusiana, Evi; Harahap, Debby Handayati; Oktariana, Desi; Prasasty, Gita Dwi (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Multidrug-resistant tuberculosis (MDR TB) is caused by Mycobacterium tuberculosis strains resistant to isoniazid and rifampicin—the most potent anti-TB drugs. Prolonged treatment duration and complex drug regimens often lead to poor adherence, contributing to high MDR TB incidence and low treatment success rates, particularly in Indonesia. This study analyzed drug utilization patterns in 52 MDR TB patients at Dr. Mohammad Hoesin Hospital Palembang, using total sampling based on medical records from October 2018 to December 2019. Data were analyzed descriptively with SPSS v25. The most common side effects reported were weakness, nausea, and vomiting (84.6%), followed by arthralgia, hyperuricemia, and hearing loss (42.3%). Severe side effects were more prevalent in the short-term regimen group (40.4%) compared to the long-term group (7.7%). Weakness, nausea, and vomiting were the most frequently observed side effects in MDR TB patients.